PENERAPAN MODEL PATUH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA: Penelitian Tindakan Kelas - Syaira, Alya Tarisa Nur; Herti Prastitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes and minimal student involvement in mathematics learning, especially on the topic of area and perimeter of flat shapes. This research uses a Classroom Action Research (CAR) approach which is implemented in four cycles of meetings, through the stages of planning, implementation, observation, and reflection in each cycle. The subjects of the research were 24 fourth-grade students of SDN Pemurus Dalam 2 Banjarmasin, consisting of 14 male students and 10 female students. Data collection techniques include observation, interviews, documentation, and learning outcome tests. The findings show that student learning completeness in the initial stage (pretest) was only 17%, then increased to 29% in the first meeting, 50% in the second meeting, 83% in the third meeting, and reached 92% in the fourth meeting. Student learning activities also increased, starting from 42% in the first meeting, rising to 63%, 83%, and reaching 96% in the final meeting. Based on these results, it can be concluded that the application of the PATUH learning model which is an integration of Problem Based Learning, Student Teams Achievement Division, and Course Review Horay has proven effective in improving the activities and mathematics learning outcomes of fourth grade students at SDN Pemurus Dalam 2 Banjarmasin